Current Account and Real Exchange Rate Dynamics in Indonesia - Firman Mochtar; Yoga Affandi (Economics and Finance in Indonesia, 2015)
We analyze the role of both permanent and temporary factors in affecting the Indonesian current account and real exchange dynamics before and after 2000. Adopting Lee and Chinn (1998; 2006) approach as well as Chinn et al. (2007), two results stand out. First, we confirm that the behavior of the real exchange rate has altered since 2000. Identifications show that permanent shocks are the primary causes for the movement of the real exchange rate after 2000, while in the period before 2000, the Indonesian real exchange rate changes are characterized by greater dominance of temporary shocks. The apparent change in the real exchange rate behavior may be strongly justified by the implementation of free-floating exchange rate system since August 1997. Second, the shift of the real exchange rate behavior after 2000 does not necessarily affect the current account dynamics. Empirical evidence confirms that the variance of current account post 2000 remains largely due to temporary shocks. Albeit having increasing influence, permanent shocks have insignificant effect in explaining fluctuations of the current account. In this sense, the current account surplus after 2000 is attributed largely to nominal variables such as price increase, while the impact of productivity improvement is still limited.Keywords: Current Account; Real Exchange Rate; Asian Crises 1997/1998AbstrakKami menganalisa peranan faktor permanen dan temporer dalam memengaruhi neraca berjalan dan dinamika nilai tukar mata uang riil Indonesia sebelum dan setelah tahun 2000. Mengadopsi pendekatan Lee dan Chinn (1998; 2006) serta Chinn et al. (2007), telah diperoleh dua kesimpulan. Pertama, kami mengonfirmasi bahwa pola nilai tukar mata uang riil telah berubah sejak tahun 2000. Identifikasi menunjukkan bahwa shock permanen adalah penyebab utama pergerakan nilai tukar mata uang riil setelah tahun 2000, sedangkan di periode sebelum tahun 2000 perubahan nilai tukar mata uang riil dicirikan oleh dominansi shock temporer. Perubahan pola nilai tukar mata uang tersebut dapat berakar dari penerapan sistem nilai tukar mengambang bebas sejak Agustus 1997. Kedua, perubahan pola nilai tukar mata uang setelah tahun 2000 tidak serta merta memengaruhi dinamika neraca berjalan. Bukti empiris mengonfirmasi bahwa variansi neraca berjalan setelah tahun 2000 tetap disebabkan utamanya oleh shock temporer. Meskipun menunjukkan peningkatan pengaruh, shock permanen memiliki pengaruh yang tidak signifikan dalam menjelaskan fluktuasi neraca berjalan. Atau dalam kata lain, surplus neraca berjalan setelah tahun 2000 dapat diatribusikan kepada variabel nominal seperti kenaikan harga, sedangkan pengaruh peningkatan produktivitas masih cenderung terbatas.Kata kunci: Neraca Transaksi Berjalan; Nilai Tukar Riil; Krisis Asia 1997/1998JEL classifications: F31; F41